Associations between persistent symptoms after mild COVID‐19 and long‐term health status, quality of life, and psychological distress. Issue 4 (28th March 2022) - Han, Jin H.; Womack, Kelsey N.; Tenforde, Mark W.; Files, D. Clark; Gibbs, Kevin W.; Shapiro, Nathan I.; Prekker, Matthew E.; Erickson, Heidi L.; Steingrub, Jay S.; Qadir, Nida; Khan, Akram; Hough, Catherine L.; et al.
Abstract: Background: We sought to assess whether persistent COVID‐19 symptoms beyond 6 months (Long‐COVID) among patients with mild COVID‐19 is associated with poorer health status, quality of life, and psychological distress. Methods: This was a multicenter prospective cohort study that included adult outpatients with acute COVID‐19 from eight sites during 2‐week sampling periods from April 1 and July 28, 2020. Participants were contacted 6–11 months after their first positive SARS‐CoV‐2 to complete a survey, which collected information on the severity of eight COVID‐19 symptoms using a 4‐point scale ranging from 0 ( not present ) to 3 ( severe ) at 1 month before COVID‐19 (pre‐illness) and at follow‐up; the difference for each was calculated as an attributable persistent symptom severity score. A total attributable persistent COVID‐19 symptom burden score was calculated by summing the attributable persistent severity scores for all eight symptoms. Outcomes measured at long‐term follow‐up comprised overall health status (EuroQol visual analogue scale), quality of life (EQ‐5D‐5L), and psychological distress (Patient Health Questionnaire‐4). The association between the total attributable persistent COVID‐19 burden score and each outcome was analyzed using multivariable proportional odds regression. Results: Of the 2092 outpatients with COVID‐19, 436 (21%) responded to the survey. The median (IQR) attributable persistent COVID‐19 symptom burden score was 2 (0, 4); higher scores were associated with lower overall health status (aOR 0.63; 95% CI: 0.57–0.69), lower quality of life (aOR: 0.65; 95%CI: 0.59–0.72), and higher psychological distress (aOR: 1.40; 95%CI, 1.28–1.54) after adjusting for age, race, ethnicity, education, and income. Conclusions: In participants with mild acute COVID‐19, the burden of persistent symptoms was significantly associated with poorer long‐term health status, poorer quality of life, and psychological distress.